Inclusive research in education: From power dynamics to data equity - Emmers, Elke; Daniels, Nicky; Saenen, Liesbet; Hermans, Katrien; Pirson, Luciano; Vaes, Merel (Sensos-e, 2025)
This methodological and theoretical article addresses the need for more inclusive research methods in educational research. Traditional research methods often neglect the perspectives of underrepresented groups. Involving participants as co-creators of knowledge leads to research and output that are not only more relevant and equitable but also contribute directly to more inclusive practices. The article examines both the theoretical foundations and practical applications of inclusive methods, focusing on the role of data equity, open science, and the challenges posed by power dynamics in research settings that frequently impede the participation of underrepresented groups. It critically reflects on and discusses how inclusive methods can effectively address these inequalities, particularly in education. It became clear that a paradigm shift is necessary to place inclusivity at the core of educational research, highlighting the importance of closer collaboration among researchers, policymakers, and practitioners.